Obesity May Be Protective against Severe Perineal Lacerations - Diana Garretto; Brian B. Lin; Helen L. Syn; Nancy Judge; Karen Beckerman; Fouad Atallah; Arnold Friedman; Michael Brodman; Peter S. Bernstein (Journal of Obesity)
Objective. To determine if there is an association between BMI and 3rd- or 4th-degree perineal lacerations in normal spontaneous and operative vaginal deliveries. Study Design. We performed a retrospective case control study using a large obstetric quality improvement database over a six-year period. Cases were identified as singleton gestations with third- and fourth-degree lacerations. Controls were obtained randomly from the database of patients without third- or fourth-degree lacerations in a 1 : 1 ratio. Univariate and multivariate logistic regression analyses were performed. Results. Of 32,607 deliveries, 22,011 (67.5%) charts with BMI documented were identified. Third- or fourth-degree lacerations occurred in 2.74% (n=605) of patients. 37% (n=223) were identified in operative vaginal deliveries. In the univariate analysis, obesity, older maternal age, non-Asian race, and birth weight <4000 g were all protective against 3rd- and 4th-degree lacerations. After controlling for age, race, mode of vaginal delivery, and birth weight, obesity remained significant. Conclusion. Being obese may protect against third- and fourth-degree lacerations independent of parity, race, birth weight, and mode of delivery.